GENETIC CHARACTERIZATION IN FOUR INDONESIAN CATTLE BREEDS INFERRED FROM ILLUMINA PARENTAGE SNP MARKERS - W.P.B. Putra; Hartati; Mariyono; R.R. Noor; C. Sumantri; E.T. Margawati (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Genetic characterization in native livestock is essential to conserve the genetics standard of livestock for pure-breeding programs. This research aimed to characterize four Indonesian cattle breeds using 156 sites of Parentage SNP Markers, includingARS-USMARC-Parent (119 sites) and ARS-USMARC (37 sites). Total of 113 mixed-sex animals were used for the evaluation, including 16 Bali (Bos javanicus), 16 Madura (Bos indicus), 33 Ongole grade (Bos indicus), and 48 Sumba Ongole (Bos indicus) cattle breeds. Results showed Bali, Madura, and Ongole lineage (Ongole grade and Sumba Ongole) cattle can be discriminated against with the Parentage SNP Markers. The pairwise genetic distance analysis revealed that Bali cattle had a closer genetic relationship with Madura cattle (0.043 - 0.151) than Ongole lineage cattle (0.073 - 0.325). However, the phylogenetic tree explained that the Ongole lineage cattle are grouped into two different clades. At the same time, Bali, Madura and Ongole lineage cattle are grouped into their original cluster. The study suggests that the Parentage SNP Markers can be used to characterize Bali, Madura, and Ongole lineage cattle accurately.